Development of Android- Based Biodiversity Learning Media on Application of A Project-Based Learning Model to Increase Student Motivation and Learning Outcomes - Muhammad Yusuf I'thisom; Saiful Ridlo (Journal of Biology Education, 2025)
The problem of low learning motivation affects student learning outcomes. This is still found in biology learning about biodiversity material in various schools, including SMA N 12 Semarang. These problems can be anticipated by implementing appropriate learning models and applying science and technology to learning. The development of Android-based learning media in project-based learning (PjBL) was chosen as an alternative problem solving. This research aims to produce Android-based learning media for biodiversity material in the application of a project-based learning model to increase student motivation and learning outcomes which is declared effective and valid for increasing student motivation and learning outcomes, as well as knowing student responses to this media. This type of research is Research and Development (R&D) with reference to the ADDIE model. Sampling in this study used a purposive random sampling technique using 2 classes as the experimental and control classes. Data collection was carried out through interviews, questionnaires, test and non-test instruments. Data were analyzed descriptively quantitatively and independently sample t-test or Mann Whitney, and N-Gain. The research results showed that the Android-based learning media developed was declared very valid and suitable for use based on the assessment of expert lecturers and teachers. Learning media was stated to be effective in increasing students' motivation and knowledge learning outcomes with moderate N-Gain, and improving students' skills, but was not effective in increasing attitude scores. The results of students' responses to the practicality of the media include quite practical criteria.